Optimization of tensile strength of PLA/clay/rice husk composites using Box‑Behnken design - Yiga, Vianney Andrew; Lubwama, Michael; Pagel, Sinja; Olupot, Peter Wilberforce; Benz, Johannes; Bonten, Christian (Biomass Conversion and Biorefinery, 2021)
Abstract It is extremely important to save costs and time while enhancing accuracy in experimentation. However, no study has utilized response surface methodology (RSM) to obtain the effects of independent parameters on properties of PLA/clay/rice husk composites. This study focused on optimization of tensile strength of fiber-reinforced polylactic acid (PLA) composites. RSM using Box-Behnken design (BBD) was used to determine optimum blending parameters of the developed composites. Fiber-reinforced PLA composites were prepared using compression molding. Rice husk fiber and clay filler were used to enhance tensile properties of PLA. Five factors, namely, clay filler loading (1 − 5 wt.%), rice husk fiber loading (10 − 30 wt.%), alkali concentration (0 − 4 wt.%), rice husk variety (K85, K98), and alkali type (NaOH, Mg(OH)2) were varied with 68 individual experiments. Tensile tests were carried out according to ASTM D638 standards. ANOVA results revealed that the quadratic models best fit the tensile strength response, with filler loading and fiber loading factors as the most significant model terms. Interaction effects were more predominant than linear and quadratic effects. The developed models used to determine maximum tensile strengths of PLA/clay/rice husk composites were in close agreement with experimental findings (R2 values of 0.9635, 0.9624, 0.9789, and 0.9731 for NaOH-modified K85 rice husks, Mg(OH)2-modified K85 rice husks, NaOH-modified K98 rice husks, and Mg(OH)2-modified K98 rice husks respectively). Individual optimal conditions were used to predict maximum tensile strengths in each set of developed composites. The predicted tensile strengths were 32.09 MPa, 33.69 MPa, 32.47 MPa, and 32.75 MPa for PLA/clay composites loaded with NaOH-modified K85 rice husks, Mg(OH)2-modified K85 rice husks, NaOH-modified K98 rice husks, and Mg(OH)2-modified K98 rice husks, respectively, which were very close to the obtained experimental values of 31.73 MPa, 33.06 MPa, 32.02 MPa, and 31.86 MPa respectively.
Keywords: Box-Behnken design; Clay; Fiber-reinforced PLA; Optimization; Response surface methodology; Rice husks; Tensile strength